Effect of source and method of application of zinc on yield and quality of black pepper (Piper nigrum L.) - Sadanandan, S Hamza, A K (Journal of Spices and Aromatic Crops, 2005)
Experiments were conducted in the green house at Peruvannamuzhi (Kerala) and also in the field at Madikeri (Karnataka) to compare the effect of zinc sources, zinc sulphate (ZnSO4) and zinc ethylenediaminetetraacetic acid chelate (Zn-EDTA) and methods of application (soil and foliar) to black pepper (Piper nigrum) in a zinc deficient soil. The results showed that with regard to soil availability of zinc, application of zinc as Zn-EDTA chelate @ 2.5 mg kg-1 soil in green house and 2.5 kg ha-1 in field conditions recorded maximum values. Leaf and berry zinc and pepper yield were maximum due to 0.5% ZnSo4 foliar spray. Irrespective of sources and methods, Zinc application significantly increased oleoresin and piperine contents. With regard to benefit : cost ratio, 0.5% foliar spray of ZnSo4 resulted in maximum value in green house, whereas soil application of 2.5 kg Zn ha-1 as ZnSo4 resulted in maximum value in field condition.